Comparative evaluation of the cyclic fatigue resistance of four Ni-Ti instruments in simulated root canal curvatures using CAD/CAM technology. - Yıldız, Tuğçenur; Zan, Recai (BMC Oral Health, 2025)
Background: This study aimed to evaluate and compare the cyclic fatigue resistance of new generation nickel-titanium file systems in simulated single and double curvature ceramic root canals. Methods: A total of 80 Nickel–Titanium (Ni-Ti) instruments—TruNatomy (TN) (26/0.04), WaveOne Gold (WOG) (25/0.07), Reciproc Blue (RecB) (25/0.08), and One Curve (OC) (25/0.04)—were tested under simulated intracanal thermal conditions (35 ± 0.1 °C). The instruments were evaluated within custom-designed artificial canals fabricated from ceramic blocks, incorporating either a single curvature (SC; 60° angle, 5 mm radius) or a double curvature configuration (DC; coronal bend: 60°, 5 mm radius; apical bend: 60°, 2 mm radius). For each instrument, the time until fracture occurred was recorded, and the number of cycles to failure (NCF) was calculated accordingly. Fragment lengths (FLs) were measured using a digital microcaliper, and the topography of the fracture surfaces was analyzed through scanning electron microscopy (SEM). Data were statistically assessed using non-parametric Kruskal–Wallis and Mann–Whitney U tests, with significance defined at the p-value threshold of < 0.05. Results: RecB files demonstrated the highest NCF in the SC group (p < 0.05). TN and OC had significantly lower NCF than RecB (p < 0.05) but were statistically similar (p > 0.05). WOG recorded the lowest NCF in SC (p < 0.05). In the DC group, WOG also showed the lowest NCF (p < 0.05), with no significant differences among the other three files (p > 0.05). SEM analysis revealed that nearly all fractured instruments exhibited a ductile fracture pattern, characterized by the presence of microcavities and pits, which are typically associated with cyclic fatigue failure. Conclusions: Selecting Ni-Ti file systems based on canal anatomy is essential for minimizing fatigue-related failures. RecB exhibited superior resistance in SC canals, while WOG showed consistently lower performance in both configurations, warranting cautious use in curved canals. These findings underscore the importance of matching instrument selection to canal morphology and mechanical demands to ensure safe and predictable clinical outcomes.